Authenticity or Self-Enhancement? Effects of Self-Presentation and Authentic Leadership on Trust and Performance - Kim, Tae-Yeol; David, Emily M.; Chen, Tingting; Liang, Yongyi (Journal of Management, 2023)
We theorized and tested an integrated model that examines the simultaneous effects of authentic self-expression and self-enhancement (including authentic and exaggerated self enhancement) on employee outcomes. Using a multisource, two-wave survey design and a sample of 143 working groups from 566 employees, we tested the indirect effects of self-presentation on job performance through (a) trust from coworkers and (b) felt trust from coworkers. We found that through trust from coworkers, authentic self-expression had a positive indirect effect on job performance, whereas authentic and exaggerated self-enhancement had negative indirect effects. Via felt trust from coworkers, authentic self-enhancement had a positive indirect effect on job performance, whereas exaggerated self-enhancement had a negative indirect effect. In addition, we identified a boundary condition of these relationships. The positive relationship between authentic self-expression and trust from coworkers and the negative relationship between exaggerated self-enhancement and trust from coworkers were stronger when working for highly authentic leaders. Contrary to expectations, the relationship between authentic self-enhancement and trust from coworkers was negative and significant when working for less authentic leaders.